Peran Praktikum untuk Meningkatkan Persepsi Mahasiswa Tentang Konsepsi Tumbuhan Tinggi di Program Studi Pendidikan Biologi: The Role of Practicum to Increase Students' Perceptions About the Conception of Higher Plants in Biology Education Study Programs - Akhmadi, Akhmadi (BiosciED: Journal of Biological Science and Education, 2024)
Abstrak. Penelitian ini bertujuan untuk mendeskripsi peran praktikum untuk meningkatkan persepsi mahasiswa Program Studi Pendidikan Biologi FKIP Universitas Palangka Raya terhadap pemahamannya tentang konsepsi Tumbuhan Tinggi. Praktikum yang diberikan berupa praktikum lapangan dan praktikum laboratorium yang relevan dengan materi teoritis. Metode penelitian yang digunakan adalah metode deskriptif dengan teknik survei eksploratif. Responden pada penelitian ini adalah semua mahasiswa program studi Pendidikan Biologi yang telah lulus mata kuliah Botani Tumbuhan Tinggi. Pengumpulan data menggunakan instrumen angket digital dengan aplikasi Google Form. Angket terdiri dari 22 butir pertanyaan yang bersifat bebas tentang konsepsi sistem klasifikasi dan ciri-ciri reproduksi Tumbuhan Tinggi. Angket berupa pertanyaan ataupun pernyataan yang dijawab dengan cara memberi tanda “cek list” (√) pada 4 alternatif jawaban. Data hasil angket dari responden mahasiswa dianalisis secara deskriptif. Hasil penelitian menyimpulkan: Praktikum berperan penting untuk meningkatkan persepsi mahasiswa Program Studi Pendidikan Biologi FKIP Universitas Palangka Raya tentang konsepsi Ciri-ciri Reproduksi Tumbuhan Tinggi, akan tetapi praktikum kurang mampu meningkatkan konsepsi Sistem Klasifikasi Tumbuhan Tinggi. Abstract. This study aims to describe the role of practical training in increasing the awareness of students of the Biology Education and Research Program, FKIP, Palangka Raya University in terms of understanding the concept of higher plants. The practical training provided is in the form of field and laboratory practices related to theoretical content. The research method used is descriptive with exploratory research techniques. All respondents in this study were students of the Biology Education Study Program who were accepted into the Advanced Plant Botany course. For data collection, we will use a digital survey tool with the Google Forms application. The questionnaire consists of 22 open-ended questions regarding the concept and characteristics of reproduction of the higher plant classification system. This survey is in the form of questions or short answers, with four choices marked with a "checklist" (√). The survey data of student respondents were analyzed descriptively. The results of the study concluded that: Although practical training has an important role in increasing the awareness of students of the Biology Education and Research Program, Faculty of Teacher Training and Education, University of Palangka Raya regarding the concept of reproductive characteristics of higher plants, not much can be done to improve the concept of reproductive characteristics. Higher plant classification system.